156k views
0 votes
Please help and thank you

Please help and thank you-example-1

1 Answer

1 vote

Answer:

D. g(x) = (x - 4)²

Explanation:

f(x) + n - shift the graph n units up

f(x) - n - shift the graph n units down

f(x - n) - shift the graph n units to the right

f(x + n) - shift the graph n units to the left

=========================================

The graph of f(x) shifted by 4 units to the right. Therefore, the equation g(x) is:

g(x) = f(x - 4) = (x -4)²

User Aaron Bertsch
by
5.2k points